Managing bipolar disorder in primary care. - Ebmeier, K (2010)
Bipolar disorder is relatively common, at least twice as common as schizophrenia, and eminently treatable. It is also perfectly suited to the well established outpatient model practised in general practice and psychiatry. All GP practices should include people with a diagnosis of bipolar disorder on their case register of people with severe mental illness. It is not possible to exclude a bipolar diagnosis categorically if there are only symptoms of depression. Most patients will have had a (hypo)manic episode by their 30s. The lifetime prevalence of bipolar affective disorder proper is 1%, with a further 1.2% presenting with milder hypomanic symptoms (so-called bipolar II disorder). Relaxing diagnostic symptom criteria increases the frequency of depressed patients who develop symptoms of mania for any length of time to 50%. The lifetime course of the illness tends to be dominated by depressive episodes: half the time is estimated to be spent in the euthymic (well) state, 12% in a manic state and 38% in a depressed state. Any depressed patient should be asked about periods in the past when (s)he has been elated in mood, found it unnecessary to sleep, talked a lot, spent excessive amounts of money etc. Treatment for bipolar disorder has to be divided into: treatment of mania, treatment of bipolar depression and prophylaxis of mood swings in either direction. Antidepressant treatments are unlikely to help manic symptoms, at worst they can precipitate or aggravate them. Antimanic treatments are unlikely to help symptoms of depression but an exception to this rule would be a genuine mood stabiliser, such as lithium. Patients with bipolar disorder should have an annual physical health review. This will include monitoring for weight gain, lipid levels, plasma glucose levels, smoking status and alcohol use, as well as blood pressure.